2021
DOI: 10.1177/0956797621995206
|View full text |Cite
|
Sign up to set email alerts
|

The Attitude–Behavior Relationship Revisited

Abstract: The attitude–behavior relationship is of great import to many areas of psychology. Indeed, psychologists across disciplines have published thousands of articles on the topic. The majority of this research implies that the attitude–behavior relationship is linear. However, observations from 4,101 participants on Amazon’s Mechanical Turk and 321,876 online reviews demonstrate that this relationship is systematically nonlinear. Across diverse topics, measures, and contexts, as attitudes move from extremely negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 57 publications
0
24
0
Order By: Relevance
“…Such analyses assume the attitude-behavior relationship is linear, although an attitude strength perspective might suggest a cubic relationship with the greatest change in behavior apparent at the extremes. Some recent research has supported a cubic relationship between attitude extremity and behavior ( Bechler et al, 2021 ), although here the greatest change in behavior was apparent around the neutral point (these tests mainly focused on the attitude-intention relationship). Bassili (1996) makes the useful distinction between operative and meta-judgmental measures of strength.…”
Section: Predictors Of Strengthmentioning
confidence: 79%
“…Such analyses assume the attitude-behavior relationship is linear, although an attitude strength perspective might suggest a cubic relationship with the greatest change in behavior apparent at the extremes. Some recent research has supported a cubic relationship between attitude extremity and behavior ( Bechler et al, 2021 ), although here the greatest change in behavior was apparent around the neutral point (these tests mainly focused on the attitude-intention relationship). Bassili (1996) makes the useful distinction between operative and meta-judgmental measures of strength.…”
Section: Predictors Of Strengthmentioning
confidence: 79%
“…Since the relationship between attitude and behavior is complex ( Bechler et al, 2021 ) and the “attitude–behavior gap” ( Kollmuss and Agyeman, 2002 , p. 246) suggests that concern about environmental problems does not necessarily mean that the corresponding behavior goes hand in hand, we used the ecological momentary assessment approach to further investigate the relationship between attitude, personality, and “green” behavior. This method minimizes recall biases and increases the ecological validity.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental attitude focuses on general cognitive and affective components of environmental protection ( Bamberg, 2003 ). In general, the assumption that attitudes shape actual behavior is widely recognized in psychological research ( Bechler et al, 2021 ). Nevertheless, the exact circumstances under which attitudes shape behavior, and to what extent, are still being researched and the relationship between attitude and behavior appears to be complex ( Bechler et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several systematic reviews have found positive effects for CPs [9], [10], [11], but little is yet known about the economic impact [1], [12]. In recent years, few studies have investigated the cost-effectiveness of ICPs, and in these studies, the patient groups and settings in which ICPs were used vary widely [13], [14], [15], [16], [17]. Recently, Everink et al [2] conducted a cohort study over a 9-month period examining intervention costs, health-care costs, and costs to patients and their families.…”
Section: Introductionmentioning
confidence: 99%